Short-Term Exercise Training Inconsistently Influences Basal Testosterone in Older Men: A Systematic Review and Meta-Analysis - Hayes, Lawrence D.; Elliott, Bradley T. (Frontiers in Physiology, 2019)
Background The age-associated decrease in testosterone is one mechanism suggested to accelerate the aging process in males. Therefore, approaches to increase endogenous testosterone may be of benefit. The aim of this paper was to undertake a Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA)-accordant meta-analysis concerning the effect of exercise on total (TT), bioavailable (bio-T), free (free-T), and salivary (sal-T) testosterone in older males. Methods Databases were searched up to and including 20th February 2018 for the terms ‘testosterone AND exercise AND aging AND males’, ‘testosterone AND exercise AND old AND males’, ‘testosterone AND training AND aging AND males’ and ‘testosterone AND training AND old AND males’. From 1259 originally identified titles, 22 studies (randomized controlled trials; RCTs; n=9, and uncontrolled trials; UCTs; n=13) were included which had a training component, participants ≥60 years of age, and salivary or serum testosterone as an outcome measure. Meta-analyses were conducted on change to testosterone following training using standardised difference in means (SDM) and random effects models. Results The overall SDM for endurance training, resistance training, and interval training was 0.398 (95% CI = 0.034 – 0.761; P = 0.010), -0.003 (95% CI = -0.330 – 0.324; P = 0.986), and 0.283 (95% CI = 0.030 – 0.535; P = 0.028) respectively. Resistance training exhibited a qualitative effect of hormone fraction whereby free-T resulted in the greatest SDM (0.253; 95% CI = -0.043 – 0.549; P = 0.094), followed by TT (0.028; 95% CI = -0.204 – 0.260; P = 0.813), and resistance training negatively influenced bio-T (-0.373; 95% CI = -0.789 – 0.042; P = 0.078). Due to the small number of studies, subgroup analysis was not possible for endurance training and interval training studies. Conclusions Data from the present investigation suggests that resistance training does not significantly influence basal testosterone in older men. Magnitude of effect was influenced by hormone fraction, even within the same investigation. Aerobic training and interval training did result in small, significant increases in basal testosterone. The magnitude of effect is small but the existing data are encouraging and may be an avenue for further research.